2014
DOI: 10.1084/jem.20132203
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of a human splenic marginal zone B cell precursor with NOTCH2-dependent differentiation properties

Abstract: Identification in humans of a bona fide marginal zone B cell population, which differentiates from a splenic marginal zone precursor through a NOTCH2 signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
123
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(143 citation statements)
references
References 48 publications
(82 reference statements)
19
123
1
Order By: Relevance
“…Furthermore, TOX deficient mice (TKO) lacked lymph nodes and had a significant decrease in the frequency and size of Peyer’s patches(40). A recent study provides data that support an important role of TOX expression in B-cell biology(41). TOX was identified as one of the top differentially expressed genes between memory B cells (IgG+ CD27+) and marginal zone B-cells (IgD+ CD27+).…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, TOX deficient mice (TKO) lacked lymph nodes and had a significant decrease in the frequency and size of Peyer’s patches(40). A recent study provides data that support an important role of TOX expression in B-cell biology(41). TOX was identified as one of the top differentially expressed genes between memory B cells (IgG+ CD27+) and marginal zone B-cells (IgD+ CD27+).…”
Section: Discussionmentioning
confidence: 89%
“…However, compared to gut ME-SW B cells, gut ME-M B cells also showed enhanced MZ-like traits (Figure 3I), including increased expression of CD21, CD35, CD1c, and the adhesion molecule CD66a (Descatoire et al., 2014, Seifert et al., 2015). Notwithstanding these similarities, supervised gene expression analysis, flow cytometry, and gene set enrichment analysis (GSEA) indicated that gut ME-M B cells were distinct from splenic MZ B cells (Figures S3B–S3E).…”
Section: Resultsmentioning
confidence: 99%
“…In mice with a conditionally targeted deletion of Notch-2 mice, their T2 precursor cells and MZ-B cells do not develop. 28 The work of Saito et al 28 has also shown that Notch-2 are preferentially expressed on mature B cells, whereas Descatoire et al 29 have shown that Notch-2 ligand Delta-Like1 expression on precursor MZ-B cells results in the development of MZ-B cells. MINT acts as a negative regulator of Notch-2, and MINT-deficient B cells differentiate more effectively into MZ-B cells.…”
Section: Developmental Origin Of Marginal Zone B Cellsmentioning
confidence: 99%